Harvesting the rubber tree once in four days; a solution to current issues in the rubber industry in Sri Lanka - Rodrigo VHL; Fernando KMEP; Kudaligama KVVS; Yapa PAJ (Journal of Rubber Research Institute of Sri Lanka, 2011)
Despite its impotance, latex harvesting in rubber plantations poses significant problems demanding high level of skilled workers and cost of production. Low frequencing harvesting harvesting (LFH) insted of traditional half spiral-once in two days system (S/2 d2), appears to be a practical solution to arrest these issue. Reduction of harvesting frequency has been limited only up to once in three days (S/2 d3) for Sri Lankan genotypes. Therefore based on some preliminary investigations, the present study was aimed at developing a suitable protocol for harvesting the rubber tree once in four days with thw half spiral cut length (S/2 d4). In addition to the small scale genotype comparison, the study comprised the commercial testing of S/2 d4 system. The overall yield given by the traditional S/2 d2 was used as the standard for the comparison and the stimulation protocol of this system was adjusted to obtain similar yields. The yield given by S/2 d4 under the stimulation protocol, applying 3.3;Ethephon (ET) once a month was comparable with that of the traditional S/2 d2 only in the wet areas of the country. Latex physiological parameters assured the sustainability of the stimulation protocol in all genotype tested except in RRIC 102. At commercial level, S/2 d4 system has resulted in 19;reduction in the cost of production, 22;increase in overall profitability, 26;increase in harvesters income and 50;reduction in worker requirement in harvesting. Potential long-term impact of this system on latex yields and socio-economic sustainability, awareness programmes and limitations of LFH in dry climates are also discussed.
Keywords: Bark consumption; COP; Latex harvesting; Latex physiology; Low frequenc tappings; Worker shortage